DESIGN AND SIMULATION OF VIRTUAL LOCAL AREA NETWORK USING CISCO PACKET TRACER - Оrdabayeva G.; Dzhsupbekova, G.; Rakhymbek, N. (Scientific Journal of Pedagogy and Economics, 2020)
Modern local networks consist of several subscriber devices located inside the same building. Computers on the local network are interconnected using network equipment - switches. By default, all devices connected to the ports of the same switch can communicate by exchanging network packets. Computer networks of data transmission are the result of the information revolution and in the future will be able to form the main means of communication. The worldwide trend towards the integration of computers in the network is due to a number of important reasons, such as the acceleration of the transmission of information messages, the ability to quickly exchange information between users, receiving and transmitting messages (faxes, E-mail letters, electronic conferences, etc.) without leaving the workplace, the ability to instantly receive any information from anywhere in the world, as well as the exchange of information between computers of different manufacturers working under different software. A large number of broadcast packets sent by devices leads to a decrease in network performance, because instead of useful operations, the switches are busy processing data addressed to everyone at once. The situation forces us to divide such large networks into autonomous subnets; as a result, the logical structures of the network are different from the physical topologies. This article discusses VLAN technology (Virtual Local Area Network - VLAN), which allows you to divide one local network into separate segments.